Long-range σ−π interactions in tetrahydro-4H-thiopyran end-capped oligo(cyclohexylidenes): photo-electron spectroscopy, ab initio SCF MO calculations, and natural bond orbital analyses - Marsman, Albert W.; Havenith, Remco W. A.; Bethke, Sabine; Jenneskens, Leonardus W.; Gleiter, Rolf; van Lenthe, Joop H.; Lutz, Martin; Spek, Anthony L. (The journal of organic chemistry, 2000)
Long-range σ−π interactions in tetrahydro-4H-thiopyran end-capped oligo(cyclohexylidenes) were identified by He(I) photoelectron spectroscopy (PES) and ab initio RHF/6-31G* calculations. The vertical ionization energies Iv,j of the highest occupied molecular orbitals (MO's) were assigned using Koopmans' theorem (Iv,j = −εj) and by correlation with the ionizations of related reference compounds. The experimental (PES) and theoretical (RHF/6-31G*) results are in good agreement. For tercyclohexylidene derivatives which contain two nonconjugated π-bonds splittings ΔIv,j of the π-bands in the range from ∼0.5 to 0.7 eV (Δ−εj ∼0.6 to 0.9 eV). For the bi- and tercyclohexylidene compounds containing two sulfur atoms at their α- and ω-end positions the π-type sulfur lone pair bands [Lpπ(S)] split significantly by ΔIv,j ∼0.3 to 0.4 eV (Δ−εj ∼0.3 to 0.4 eV), i.e. σ−π interactions over distances of ca. 8 and 12 Å, respectively, occur. The magnitude of the interactions and the observed splittings are independent of the anti and syn conformations of the oligo(cyclohexylidene) hydrocarbon skeletons. RHF/6-31G* Natural Bond Orbital analyses reveal that the Hax−C−C−Hax precanonical MO's (PCMO's) centered on the cyclohexyl-type rings are paramount for the relay of the through-bond σ−π interactions; no through-space σ−π interactions were identified.